Breast-Gynaecological & Immuno-Oncology International Cancer Conference (BGICC) Consensus and Recommendations for the Management of Triple-Negative Breast Cancer - GÜLLÜOĞLU, MAHMUT BAHADIR (MDPI, 2021)
Simple Summary Despite the impressive progress in the treatment of triple-negative breast cancer (TNBC), oncologists still face several provocative clinical scenarios in daily practice where clear evidence-based recommendations are lacking, and expert opinion is of utmost importance. In an attempt to seek guidance for these controversial topics in TNBC management, a consensus recommendations session for TNBC was held during the 12th round of the Breast-Gynaecological & Immuno-oncology International Cancer Conference (BGICC) Egypt, 2020. This special session convened a multidisciplinary committee of 35 panellists who specialize in breast cancer care from 13 countries. The consensus covered all the aspects of TNBC management starting from defining TNBC to the management of metastatic disease and highlighted the rapidly evolving landscape in this field. Consensus was reached in 70% of the statements (35/50). In addition, areas of warranted research were identified to guide future prospective clinical trials. Background: The management of patients with triple-negative breast cancer (TNBC) is challenging with several controversies and unmet needs. During the 12th Breast-Gynaecological & Immuno-oncology International Cancer Conference (BGICC) Egypt, 2020, a panel of 35 breast cancer experts from 13 countries voted on consensus guidelines for the clinical management of TNBC. The consensus was subsequently updated based on the most recent data evolved lately. Methods: A consensus conference approach adapted from the American Society of Clinical Oncology (ASCO) was utilized. The panellists voted anonymously on each question, and a consensus was achieved when >= 75% of voters selected an answer. The final consensus was later circulated to the panellists for critical revision of important intellectual content. Results and conclusion: These recommendations represent the available clinical evidence and expert opinion when evidence is scarce. The percentage of the consensus votes, levels of evidence and grades of recommendation are presented for each statement. The consensus covered all the aspects of TNBC management starting from defining TNBC to the management of metastatic disease and highlighted the rapidly evolving landscape in this field. Consensus was reached in 70% of the statements (35/50). In addition, areas of warranted research were identified to guide future prospective clinical trials.
Keywords: triple-negative breast cancer; consensus; immunotherapy; BRCA mutations; platinum; TUMOR-INFILTRATING LYMPHOCYTES; COMPLETE RESPONSE PCR; DISEASE-FREE SURVIVAL; RANDOMIZED PHASE-III; LOCOREGIONAL RECURRENCE; NEOADJUVANT CHEMOTHERAPY; ADJUVANT CHEMOTHERAPY; MUTATION CARRIERS; AMERICAN SOCIETY; POSTMASTECTOMY RADIOTHERAPY